2011
DOI: 10.2337/diaspect.24.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Non-Periodontal Oral Manifestations of Diabetes: A Framework for Medical Care Providers

Abstract: In Brief In addition to periodontitis and dental caries, other oral conditions commonly occur commonly in patients with diabetes. These include fungal infections, salivary gland dysfunction, neuropathy, and mucosal disorders. Many of these lesions can be easily examined and documented by non-dental providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 45 publications
(25 reference statements)
1
33
0
4
Order By: Relevance
“…Studies by Wang et al have shown abnormal subcellular localization of AQP5 as well as downregulation of AQP5 protein in parotid glands of STZ‐induced diabetic rats 23 . Previous research in humans has shown that salivary flow rate is reduced in the onset of DM 3 , 4 . In the current study, the authors also found that the salivary volume and weights of all three salivary glands (P, SM, SL) were less in the DB rats compared with controls.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Studies by Wang et al have shown abnormal subcellular localization of AQP5 as well as downregulation of AQP5 protein in parotid glands of STZ‐induced diabetic rats 23 . Previous research in humans has shown that salivary flow rate is reduced in the onset of DM 3 , 4 . In the current study, the authors also found that the salivary volume and weights of all three salivary glands (P, SM, SL) were less in the DB rats compared with controls.…”
Section: Discussionsupporting
confidence: 71%
“…DM‐induced oral health problems are highly prevalent in minority populations, particularly African Americans, Hispanics, and American Indians 2 . DM is thought to promote xerostomia, a qualitative or quantitative absence of saliva in the oral cavity 3 , 4 . Decreased salivary flow can cause complications in the oral cavity by allowing excessive accumulation of bacteria, leading to numerous oral infections, extreme thirst (especially at night), alteration in the taste of food, rampant tooth decay, and halitosis 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective oral dryness may not be associated with hyposalivation (López-Pintor et al, 2016). It may be due to thirst, dehydration, side effects of concomitant drug therapy that is commonly used by diabetic patients as antihypertensive drugs and diuretics (Gandara and Morton, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly periodontal infections are more commonly observed in diabetic individuals [2]. Diabetes negatively affects the salivary gland function and immune function which further increases the risk of oral infections in these individuals [3,4]. Oral infections including hyposalivation or xerostomia which is associated with burning sensation of mouth, loss of sensation of taste, enlargement of salivary glands, candida infections, and few autoimmune lesion such as lichen planus are reported [1].…”
Section: Introductionmentioning
confidence: 99%